2022
DOI: 10.3389/fphar.2022.990586
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of zinc oxide nanoparticles on spinal cord injury

Abstract: The microenvironmental changes in the lesion area of spinal cord injury (SCI) have been extensively studied, but little is known about the whole-body status after injury. We analyzed the peripheral blood RNA-seq samples from 38 SCI and 10 healthy controls, and identified 10 key differentially expressed genes in peripheral blood of patients with SCI. Using these key gene signatures, we constructed a precise and available neural network diagnostic model. More importantly, the altered transcriptome profiles in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…A recent, for instance, showed that ZnO NPs exerted neuroprotective actions in spinal cord injury. Following the administration of ZnO NPs, the researchers saw a reduction in oxidative stress levels and rescuing the neuronal apoptosis 41 aligning with another study in 2022, that showed ZnO NP possessed neuroprotective action by reducing the basal levels of reactive oxygen species, Bax/Bcl-2 mRNA ratios, p53 and apoptosis brought by 6-OHDA in SH-SY 5Y cells (neuroblastoma cell line) 42 . Another study in 2012, explored the neuroprotective effects of ZnO NP on spatial cognition and synaptic plasticity in mice with depressive-like behaviors 32 .…”
Section: Discussionsupporting
confidence: 67%
“…A recent, for instance, showed that ZnO NPs exerted neuroprotective actions in spinal cord injury. Following the administration of ZnO NPs, the researchers saw a reduction in oxidative stress levels and rescuing the neuronal apoptosis 41 aligning with another study in 2022, that showed ZnO NP possessed neuroprotective action by reducing the basal levels of reactive oxygen species, Bax/Bcl-2 mRNA ratios, p53 and apoptosis brought by 6-OHDA in SH-SY 5Y cells (neuroblastoma cell line) 42 . Another study in 2012, explored the neuroprotective effects of ZnO NP on spatial cognition and synaptic plasticity in mice with depressive-like behaviors 32 .…”
Section: Discussionsupporting
confidence: 67%
“…Shao and co-workers looked into the therapeutic potential of ZnO NPs using an in vitro brain axotomy model. After an axotomy, it was demonstrated that ZnO NPs may function as a neuroprotective agent to lower oxidative stress levels and finally restore neuronal apoptosis . Due to their non-zero band gap and large surface area, the luminescent GQDs exhibit excellent optoelectronic properties. , Because it modifies the charges in the sp 2 carbon network of GQDs, therefore successfully controlling the local chemical characteristics and bandgaps, nitrogen has been considered one of the most studied dopants for carbon-based nanomaterials, influencing its electrical and optical properties .…”
Section: Introductionmentioning
confidence: 99%